Perancangan alat bantu untuk memperbaiki proses perencanaan produksi pada PT X - Hans Gerald Regawa (Universitas Kristen Maranatha, 2019)
Production planning is part of the operational management that is important in a company. By managing production planning properly, the production process in a company will be able to run better. PT X is a company that produces vehicle spareparts for private cars. The company runs make to order system to fulfill the production procss. In the make to order system, a new product will begin to be produced by the company if there is an order from the customer. In this system, a company has inventory i.e. raw material and work in process. The problem are PT X have lack of raw materials and the absence of lead time given by the company to customers about when a product will be sent. To overcome this problem, improvements are made to the existing production planning system. Improvements begin by changing the way raw materials are purchased. This is done by treating the system with order point. With this system, company will never experience a shortage of raw materials because when raw material below order point, company must immediately order new raw materials. Thus the production process will not be disturbed and can run smoothly. In determining when a product will be completed and sent to customers, a production planning system with DSS tools (decision support system) is made using Microsoft Excel tools. By using DSS, the system will automatically display when a product will be finished and when it can be sent to the customer, when to buy raw materials, and how much production order is. Accordingly, the company can provide certainty of information to customers when the products have been produced and shipped.